Female Identity and Imposed Codes in Caroline Compson: The Influence of Utopia on a Mother - Daniello Edda (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
This article will focus on female identity and the codes imposed on the character of Caroline Compson in William Faulkner's novel "The Sound and the Fury." The complexity of her character is evident throughout the novel. The characters her children portray in the story reflect the authority Caroline Compson had over their upbringing. Faulkner creates an individual, a symbol of a specific philosophy about the world, specifically that of South America. Under the influence of cultural codes imposed by racial aggression and class superiority, she had to adapt to the rules of such a reality. Caroline initiates a utopian image for her life and, above all, a utopian image for the behavior of every woman based on the cultural codes of this society and religious myth. They imposed a utopia of motherhood. Physical purity is at the heart of her being, which is even emotional. Apart from love, neglect, and deadly tyranny, a woman's failure is hidden. Buried in her utopia, she abandons physical desire and attention to her husband and children. Through an empirical analysis of Caroline Compson, I will arrive at the point of evaluating her identity and the codes that disturb her children and her husband.